ANALISIS KOMUNIKASI PEMASARAN GRACE AND GLOW MELALUI KANAL MEDIA SOSIAL TIKTOK (Universitas Negeri Surabaya, 2023)
Online marketing has now become a strategy that is widely used by various brands, including beauty brands. This was also adopted by the Grace and Glow brand. As one of the beauty products that started producing its products in the 2020 pandemic, grace and glow uses a lot of the power of sosial media tiktok in marketing its products. This study aims to find out how the digital marketing communication is carried out by the Grace and Glow team through tiktok content and managing the tiktok account @graceandglow.id. The research method used was the use of descriptive content analysis, which used data analysis and processing of data taken from the research object, namely the grace and glow tiktok account during the period of one month of research. The result of this study is that Grace and Glow uses TikTok as a promotional medium as well as sales for their products, by producing a lot of content containing the theme